2018
DOI: 10.1016/j.dark.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Implications of minimum and maximum length scales in cosmology

Abstract: We investigate the cosmological implications of the generalized and extended uncertainty principle (GEUP), and whether it could provide an explanation for the dark energy. The consequence of the GEUP is the existence of a minimum and a maximum length, which can in turn modify the entropy area law and also modify the Friedmann equation. The cosmological consequences are studied by paying particular attention to the role of these lengths. We find that the theory allows a cosmological evolution where the radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…Nonetheless, a negative GUP parameter has interesting implications, see e.g. [28,[38][39][40][41]. For the purposes of this work, we found that allowing α L to be negative leads to the unphysical result H (z) < 0.…”
Section: Implementing the Friedmann Equationsmentioning
confidence: 66%
See 2 more Smart Citations
“…Nonetheless, a negative GUP parameter has interesting implications, see e.g. [28,[38][39][40][41]. For the purposes of this work, we found that allowing α L to be negative leads to the unphysical result H (z) < 0.…”
Section: Implementing the Friedmann Equationsmentioning
confidence: 66%
“…To the best of our knowledge, there are very few studies that aim to constrain the GUP parameter with cosmological observations. One of them is [28], which makes use of the apparent horizon formalism to inquire whether the GUP effects could account for dark energy. However, the author mostly deals with an alternative formulation of the GUP, the General Extended Uncertainty Principle (GEUP), which predicts the existence of a maximum length as well as a minimum one.…”
Section: Experimental Bounds On Gupmentioning
confidence: 99%
See 1 more Smart Citation
“…In [4] the authors use GEUP to show that a non-zero cosmological constant can restore the Chandrasekhar limit. Effects of GEUP in cosmology has been studied in [56]. Modified uncertainty principles that induce a maximum length have been employed in order to describe the cosmological particle horizon [57].…”
Section: Introductionmentioning
confidence: 99%
“…This modified uncertainty principle has terms proportional to even powers in the position uncertainty [58]. Cosmological observational data have been used to obtain constraints for GUP parameters [21,42,48,56,59]. 2 The 3rd quantization consists of initially considering the Wheeler-DeWitt equation as a classical equation of a classical field (the wave function of the Universe in the 2nd quantization) which then is turned an operator.…”
Section: Introductionmentioning
confidence: 99%